Racial Diversity and Firm Performance: The Mediating Role of Competitive Intensity. (March 2014) - Andrevski, Goce; Richard, Orlando C.; Shaw, Jason D.; Ferrier, Walter J.
The authors examine the mediating role of competitive intensity in the relationship between managerial racial diversity and firm performance (i.e., market share gain and average stock return). Racial diversity relates to firm performance via firms' capacity to compete intensively (i.e., to introduce new competitive actions frequently). An analysis reveals that environmental munificence moderates competitive intensity's mediating effect: Racially diverse management groups compete more intensively and perform better when they compete in munificent environments. The authors also find support for a moderated mediation model that simultaneously tests all components of their framework.